LNG in the Northwestern Coast of Mexico: Impact on Natural Gas on Both Sides of the U. S.-Mexico Border - Meritet, Sophie; Rosellón, Juan; Elizalde, Alberto (Frontera Norte, 2017)
This paper studies the possible impacts of liquefied natural gas (LNG) projects on natural gas prices on both sides of the U. S.-Mexico border in California. In that state gas prices are high and demand is expected to grow. Several projects for LNG facilities have been proposed and have to cope with public opinions against them. In Baja California, four LNG projects are under development given the rising demand forecasted for the next years. After a detailed study of the opportunity for LNG projects, we conclude with an analysis of the fundamentals of the current and future price formation in both sides of the U. S.- Mexico border. RESUMEN Este artículo estudia los posibles impactos de los proyectos de gas natural licuado (GNL) sobre los precios del gas natural en ambos lados de la frontera Estados Unidos-México en el área de California. En California, los precios son altos y la demanda se espera que crezca. Varios proyectos de instalaciones de GNL han sido propuestos y tienen que lidiar con opiniones públicas en su contra. En Baja California, cuatro proyectos de GNL están en desarrollo, dada la alta demanda pronosticada para los años siguientes. Después de un estudio detallado de las oportunidades para proyectos de GNL, concluimos con un análisis de los fundamentos de la formación actual y futura de precios en ambos lados de la frontera.